2019
DOI: 10.1016/j.humov.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Stability of pace and turn parameters of elite long-distance swimmers

Abstract: A B S T R A C TThis study aimed to assess the stability of the performance, pace and turn parameters of elite long-distance male swimmers during an 800 m freestyle race. The sample was composed by 38 male swimmers, participating in the 800 m event at the 2016 LEN European Aquatic Championships (long course meter). The performance, and a set of pace and turn parameters were analyzed. A customized software was used to perform each race analysis. Swimmers spent 64.05 ± 0.50% and 35.95 ± 0.49% of the final race ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 15 publications
(17 reference statements)
2
33
0
Order By: Relevance
“…Studies can be found in the literature about pacing in 800 m freestyle events (Lipinska et al, 2016a;Morais et al, 2019a), and 1500 m freestyle events (Lipinska et al, 2016b;Lipinska & Erdmann, 2009;Oliveira et al, 2019). Overall, they showed that parabolic pacing is generally used in freestyle events of 800 m and 1500 m, with the highest swimming speed at the beginning and end of the race.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Studies can be found in the literature about pacing in 800 m freestyle events (Lipinska et al, 2016a;Morais et al, 2019a), and 1500 m freestyle events (Lipinska et al, 2016b;Lipinska & Erdmann, 2009;Oliveira et al, 2019). Overall, they showed that parabolic pacing is generally used in freestyle events of 800 m and 1500 m, with the highest swimming speed at the beginning and end of the race.…”
Section: Introductionmentioning
confidence: 98%
“…In swimming, there are studies that video-analysed the swimmers' performances in major events such as the Olympic Games (e.g., Arellano et al, 2001;Hellard et al, 2008), World Championships (e.g., Simbaña-Escobar et al, 2018a;Veiga & Roig, 2016), and European Championships (e.g., Morais et al, 2019a). In a swimming race the performance includes the start, clean swim, turn(s), and finish (Hay & Guimaraes, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations